UNIT 7.32 Uncompensated Polychromatic Analysis of Mitochondrial Membrane Potential Using JC‐1 and Multilaser Excitation. Issue 1 (1st April 2015) - De Biasi, Sara; Gibellini, Lara; Cossarizza, Andrea
Abstract : The lipophilic cation JC‐1 (5, 5′, 6, 6′‐tetrachloro‐1, 1′, 3, 3′‐tetraethyl‐benzimidazolyl carbocyanine iodide) has been used for more than 20 years as a specific dye for measuring mitochondrial membrane potential (ΔΨm ). In this unit, we revise our original protocol (that made use of a single 488 nm laser for the detection of monomers and aggregates, and where compensation was an important step) to use dual‐laser excitation. Moreover, thanks to recently developed multilaser instruments and novel probes for surface and intracellular markers, JC‐1 can be utilized by polychromatic flow cytometry to simultaneously detect, without any compensation between fluorescences, ΔΨm along with other biological parameters, such as apoptosis and the production of reactive oxygen species. © 2015 by John Wiley & Sons, Inc.